Anti-inflammatory and anti-allergic activity of the methanolic extract from Annona sylvatica (Annonaceae) - Andrade-Silva, M.; Cavalher-Machado, S. C.; Formagio, A. S. N.; Maris, R. S.; Lima Junior, O. M. de; Mello, S. B. de; Henriques, M. G. M. O.; Arena, A. C. [UNESP]; Kassuya, C. A. L. (Funpec-editora, 2020)
Annona sylvatica (Annonaceae) is a common medicinal plant used in folk medicine for fever and cough; it is found in several Brazilian states, including Mato Grosso do Sul. The local population uses A. sylvatica leaves for treating fever and cough; however, how this medicinal plant affects the patients is little understood. We evaluated the anti- inflammatory and anti-allergic properties of a methanolic extract of A. sylvatica (MEAS) leaves in mouse models of inflammation and allergy. The study employed male C57bL/6 mice for allergy models and male Swiss mice for the inflammation study. Oral treatments with MEAS (30 to 150 mg/kg) significantly inhibited the carrageenan- induced leukocyte migration and protein extravasation to the cavity in an air pouch model. In the allergic animal models, oral treatment with MEAS (150 mg/kg) significantly reduced histamine- and ovalbumin (OVA)-induced paw edema. Moreover, in the OVA-induced allergic lung inflammation model, oral treatment with MEAS (150 mg/kg) significantly inhibited neutrophil, eosinophil, and mononuclear cells migration to the lung. Pretreatment of neutrophils with MEAS (3, 150, 300 mu g/mL) significantly reduced neutrophil chemotaxis induced by NFormyl-Met-Leu- Ph (fMLP) and complement 5a (C5a, in a concentration-dependent manner. We conclude that A. sylvatica has antiinflammatory and anti-allergic properties. Flavonoids and acetogenins, compounds found in the MEAS, could be responsible for these antiinflammatory and anti-allergic effects.
Keywords: Araticum; Allergy; Inflammation; Ovalbumin; Air pouch; Histamine